A biodiverse entrepreneurship-based textbook: A media of students’ entrepreneurship enthusiasm development - Nur Hayati; Lina Arifah Fitriyah (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
In the natural science education study program of Universitas Hasyim Asy'ari Jombang UNHASY, textbooks based on biodiversity have never been developed and applied to biotechnology courses. This study aims to reveal the appropriateness of biodiverse entrepreneurship-based textbook based on validity and effectivity. This development model is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The study instruments include validation sheets, learning outcomes assessment sheets, and entrepreneurship enthusiasm questionnaire. The validity percentage average by the material experts is 77, 08% with valid criteria. The validity percentage average by the media experts is 73, 6% with valid criteria. The result of the validity test by user, showed the average is 83, 4% with valid criteria. Next, the effectivity test showed that the classical completeness score is 73, 7% with good criteria and the percentage average of the entrepreneurship enthusiasm is 83, 95% with high criteria. It is concluded that the biodiverse entrepreneurship-based textbook is effective for developing students’ entrepreneurship enthusiasm.